2020
DOI: 10.1021/acsphotonics.0c01559
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electric Field-Induced Phase Transition in Bulk Bi0.5Na0.5TiO3 under High-Intensity Terahertz Irradiation

Abstract: Ultrafast polarization switching is being considered for the next generation of ferroelectric-based devices. Recently, the dynamics of the field-induced transitions associated with this switching have been difficult to explore, due to technological limitations. The advent of terahertz (THz) technology has now allowed for the study of these dynamic processes on the picosecond (ps) scale. In this paper, intense THz pulses were used as a high-frequency electric field to investigate ultrafast switching in the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In a number of studies it was shown that THz radiation can also efficiently manipulate properties of materials, for example inducing subpicosecond changes of the macroscopic polarisation in organic ferroelectrics, [130] a phase transition in atomic caesium vapor, [131] an ultrafast phase transition from weak polar (Cc) to strong polar (R3c) phases in ferroelectric Bi 0.5 Na 0.5 TiO 3 , [132] a THz-driven irreversible topological phase transition in two-dimensional MoTe 2, [133] and a THz induced insulator-to-metal transtion in VO 2 -based metamaterials. [134] In most of these examples reasonably strong THz fields were used.…”
Section: Future Researchmentioning
confidence: 99%
“…In a number of studies it was shown that THz radiation can also efficiently manipulate properties of materials, for example inducing subpicosecond changes of the macroscopic polarisation in organic ferroelectrics, [130] a phase transition in atomic caesium vapor, [131] an ultrafast phase transition from weak polar (Cc) to strong polar (R3c) phases in ferroelectric Bi 0.5 Na 0.5 TiO 3 , [132] a THz-driven irreversible topological phase transition in two-dimensional MoTe 2, [133] and a THz induced insulator-to-metal transtion in VO 2 -based metamaterials. [134] In most of these examples reasonably strong THz fields were used.…”
Section: Future Researchmentioning
confidence: 99%
“…Therefore, the higher dielectric permittivity and loss of the Non‐LTD 1700 ceramics can be attributed to a possible long distance between YZr and VO..in the oxygen vacancy associated (YZrVO..) dipoles. Zhang et al 20 . have shown that a longer dipole (e.g., a longer distance between YZr and VO..0.28em in our samples) may produce a higher permittivity under the same AC electric field.…”
Section: Resultsmentioning
confidence: 56%
“…43 Therefore, the higher dielectric permittivity and loss of the Non-LTD 1700 ceramics can be attributed to a possible long distance between 𝑌 ′ 𝑍𝑟 and 𝑉 .. 𝑂 in the oxygen vacancy associated (𝑌 ′ 𝑍𝑟 − 𝑉 .. 𝑂 ) dipoles. Zhang et al 20 have shown that a longer dipole (e.g., a longer distance between 𝑌 ′ 𝑍𝑟 and 𝑉 .. 𝑂 in our samples) may produce a higher permittivity under the same AC electric field. The long 𝑌 ′ 𝑍𝑟 − 𝑉 .. 𝑂 distance is also related to a loosely packed structure of dipoles in the ceramic sintered at 1700…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The suppression of the phase transition was mainly attributed to kinetic effects and partially to the self-heating of the sample, whose temperature exponentially increased with increasing frequency and further prevented a long-range ferroelectric state to be established [221]. However, recent experiments have demonstrated that the application of THz electric field pulses of about 155 kV/cm intensity at 200 K for a time duration as short as 20 ps on BNT ceramics produces detectable changes in reflectivity, which are due to a structural transition from the monoclinic weakly polar phase Cc to the strongly polar phase R3c [222]. Although, the extent of the THz field-induced transition is lower than that driven under DC poling conditions, these results indicate that the BNT structure is also able to transform under THz irradiation [222].…”
Section: Frequency/rate Dependence Of Electric Field-induced Transfor...mentioning
confidence: 99%